International diversification and the South African investor - R. Van Den Honert; J. F. Affleck-Graves (South African Journal of Business Management, 1985)
In the event of a relaxation or scrapping of the current exchange control regulations, the South African investor could consider an investment in foreign stocks or commodities as well as local stocks. In this article two approaches to the assessment of the past performance of various local and foreign security markets are considered. Initially the past performance of 24 markets are studied individually and their returns and corresponding risks are examined, with special reference to the exchange rate factor. Secondly the statistical technique of multidimensional scaling is applied to the 24 markets. Since portfolio diversification is a fundamental aim of any rational investor, securities from markets which exhibit dissimilar price movements would be favourable for inclusion in a portfolio. The method of multidimensional scaling results in a map-like picture which gives the investor a visual display of those markets which move together (i.e. limited diversification opportunities) and those that move differently (i.e. provide good diversification opportunities).
Keywords: 650